Cure [compact disc, unabridged] - Cook, Robin 1940- (Penguin Audio, 2010)
With her son's neuroblastoma in remission, New York City medical examiner Laurie Montgomery returns to work, only to face the case of her career: the investigation into the death of CIA agent Kevin Markham. Markham's autopsy results are inconclusive, and though it appears he's been poisoned, toxicology fails to corroborate Laurie's suspicions. She enlists the help of her husband, Jack Stapleton, and together they must race to crack the case before they're consumed in a game of biotech espionage.